1984
DOI: 10.1128/iai.45.2.447-452.1984
|View full text |Cite
|
Sign up to set email alerts
|

Activation of murine polymorphonuclear neutrophils for fungicidal activity with supernatants from antigen-stimulated immune spleen cell cultures

Abstract: An in vitro model of in vivo immunological activation of murine polymorphonuclear neutrophils (PMN) was developed. Culture supernatants of spleen cells from Blastomyces dermatitidis-immunized mice stimulated with B. dermatitidis antigens in vitro were studied. Incubation of the supernatants with thioglycolate-elicited PMN enabled the cells to significantly reduce (31 +/- 6%) B. dermatitidis inoculum CFU. Optimum production of active supernatants occurred after 4 to 6 days of stimulation in vitro and required 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…Evidence has accumulated that indicates that polymorphonuclear neutrophils (PMN) are functionally a heterogenous population (24,25). Furthermore, the metabolic activity of PMN has been reported to be enhanced during gram-negative bacterial infections (12,18), elicitation in immune mice with antigen (5), or treatment in vitro with supernatants from either mitogen (4,7,11) or antigen-stimulated lymphocyte cultures (4). Enhancement of PMN metabolic activity associated with gram-negative bacterial infections was measured by increased reduction of nitro-blue tetrazolium (12,18) or by chemiluminescence (CL) (2) upon interaction with opsonized zymosan.…”
mentioning
confidence: 99%
“…Evidence has accumulated that indicates that polymorphonuclear neutrophils (PMN) are functionally a heterogenous population (24,25). Furthermore, the metabolic activity of PMN has been reported to be enhanced during gram-negative bacterial infections (12,18), elicitation in immune mice with antigen (5), or treatment in vitro with supernatants from either mitogen (4,7,11) or antigen-stimulated lymphocyte cultures (4). Enhancement of PMN metabolic activity associated with gram-negative bacterial infections was measured by increased reduction of nitro-blue tetrazolium (12,18) or by chemiluminescence (CL) (2) upon interaction with opsonized zymosan.…”
mentioning
confidence: 99%
“…T cells are important regulators of the innate, as well as cognate, immune response. T cells produce lymphokines capable of activating macrophages, natural killer cells, and polymorphonuclear cells for efficient killing of infectious agents [34,35]. T lymphocytes are also important in pulmonary immune responses, which is the target organ for many Pseudomonas infections.…”
Section: Discussionmentioning
confidence: 99%
“…Because cognate immunity, specifically T cells, has been demonstrated to influence both innate and specific effector functions [3][4][5], attention has more recently focused on the contribution of T cells as critical orchestrators of lung defense. Perhaps as a consequence of their importance in coordinating the immune response in the pulmonary compartment, T cells are often targeted by infectious agents to produce a disproportionately heightened and undirected inflammatory response [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, PMN activation by lymphokines has been reported by a number of investigators. For example, Brummer and Stevens reported that treatment with lymphokine-rich culture supernatants induced fungicidal activity of PMNs [17]. Cross et al reported that a human cell line could release a PMN-activating factor which enhanced PMN migration and oxygen production [18].…”
Section: Discussionmentioning
confidence: 99%